DAMPAK UNDANG-UNDANG CIPTA KERJA (OMNIBUS LAW) BAGI PERIZINAN KEGIATAN USAHA DAN INVESTASI DI INDONESIA - Syahrial, Aditya Bhatara; Ramadhan, Akbar; Muharrikatiddiniyah, Nur; Bustani, Simona (Ensiklopedia of Journal, 2024)
The introduction of the Job Creation Law by the Indonesian government is a strategic measure that will impact the licensing and investment framework in Indonesia.The law is expected to streamline the licensing process, accelerate investment, and create a more friendly business environment for domestic and foreign investors.One of the main focuses of the Job Creation Act is licensing reform, particularly in relation to investments in Indonesia.These include simplifying the number of permits required to carry out investment activities in Indonesia, simplifying the licensing process, and introducing a risk-based licensing system.These measures taken by the government are expected to improve efficiency and increase investor enthusiasm for investment activities in Indonesia.However, the implementation of the Job Creation Act also generated debate and controversy.Some parties are concerned that lowering labor and environmental standards or changing regulations too quickly could have negative social and environmental impacts.Therefore, the discussion in this journal is about the process of changing these simplifications, the impact of which will affect Indonesia's investment environment, especially at the international market level.Keywords : Omnibus Law, Licensing, Investment